Enhancing Tamoxifen Therapy with α-Mangostin: Synergistic Antiproliferative Effects on Breast Cancer Cells and Potential Reduced Endometrial Impact - Rafael Vargas-Castro; Rocío García-Becerra; Lorenza Díaz; Euclides Avila; David Ordaz-Rosado; Samantha V. Bernadez-Vallejo; Saúl Cano-Colín; Javier Camacho; Fernando Larrea; Janice García-Quiroz (MDPI AG, 2023)
Breast cancer is the most prevalent neoplasia among women worldwide. For the estrogen receptor-positive (ER+) phenotype, tamoxifen is the standard hormonal therapy; however, it carries the risk of promoting endometrial carcinoma. Hence, we aimed to evaluate the antiproliferative effect of the phytochemical α-mangostin (AM) as a co-adjuvant alongside tamoxifen on breast cancer cells to improve its efficacy while reducing its adverse effects on endometrium. For this, ER+ breast cancer cells (MCF-7 and T-47D) and endometrial cells (N30) were treated with AM, 4-hydroxytamoxifen (4-OH-TMX), and their combination. Cell proliferation was evaluated using sulforhodamine B assay, and the pharmacological interaction was determined through the combination index and the dose reduction index calculation. The genes KCNH1, CCDN1, MKI67, and BIRC5 were amplified by real-time PCR as indicators of oncogenesis, cell cycle progression, cell proliferation, and apoptosis, respectively. Additionally, genes involved in ER signaling were analyzed. In breast cancer cells, the combination of AM with 4-OH-TMX showed a synergistic antiproliferative effect and favorable dose reduction. AM and 4-OH-TMX decreased KCNH1, CCND1, and BIRC5 gene expression. In endometrial cells, AM decreased MKI-67 gene expression, while it reverted the 4-OH-TMX-dependent CCND1 upregulation. This study establishes the benefits of incorporating AM as a co-adjuvant for first-line ER+ breast cancer therapy.